The Use of Blockchain in Aviation Safety Reporting Systems: A Framework Proposal. Issue 4 (2nd October 2022) - Aktas, Ersin; Demir, Sercan; Paksoy, Turan
ABSTRACT: Objective: The purpose of this study is to propose a blockchain-based framework for designing an incident reporting system in aviation. Background: The incident reporting system plays a key role in ensuring safety. It helps to obtain safety-related data and to eliminate unsafe situations before they turn into accidents. Keeping safety information permanently and in unchangeable form, tracking all the transactions regarding unsafe situations, and providing feedback to all parties have great importance for the efficiency of the system. Therefore, the reporting system should be designed with appropriate technology. Blockchain, a digital ledger, offers a decentralized, transparent, and flexible infrastructure for various implementation areas. As a breakthrough in software technology, blockchain significantly supports many design aspects of the incident reporting system. Method: The literature on three related areas, incident reporting, organizational memory, and blockchain technology, were reviewed. Later, the main requirements for effective safety reporting were identified. Finally, the extent to which blockchain technology meets these requirements was delineated by a proposed framework. Findings: The proposed framework mainly brings full transparency and accountability in incident analysis, increases the effectiveness of the feedback mechanism, and strengthens confidentiality. In addition, this framework enables the creation of a robust safety memory. Conclusion: This study indicated that blockchain offers a suitable design technology for incident reporting, contributing, security, transparency, and anonymity aspects of the incident reporting system.